Good perception of own lifestyle associated with poor attendance at Diabetic RetinaScreen Programme. (20th October 2021) - Syed, S; Fitzpatrick, P
Abstract: Background: Untreated diabetic retinopathy is the most common cause of sight loss in people of working age. The Diabetic RetinaScreen programme (DRS) is the national diabetic retinopathy screening programme in Ireland which commenced in 2013 with aim to prevent diabetic retinopathy and subsequent blindness, through free screening and ophthalmology services. High uptake is crucial for the effectiveness of the programme. This study aimed to determine the sociodemographic, lifestyle and healthcare factors associated with attendance at the DRS programme in Ireland, using data from a national cohort study, the Irish Longitudinal Study on Ageing (TILDA). Methods: The TILDA wave-4 dataset (anonymised) was utilised for the current study. Questions on DRS invitation and attendance formed part of the wave 4 study questionnaire. Multivariate logistic regression was used to examine independent factors associated with attendance. SPSS was used for analysis. Results: 418 respondents (7.3%) were invited to DRS and 373 (89.2%) attended. Among all those who were invited to DRS, 244 (58.4%) were male and 174 (41.6%) were female. The mean age was 69.8 years (53-84 years). Following multivariate logistic regression, following a good diet/taking exercise (OR = 0.29, 95% CI 0.10-0.82) was negatively associated with attendance, after adjustment for age, male gender, higher education and medical card. Conclusions: Recognising factors linked with uptake is important to develop goal directed strategies. Interestingly those who stated they followed a good diet & took exercise and were compliant with DM prevention were less likely to attend DRS. Previous research has also indicated that a higher physical activity level is associated with higher self-perceived health status Key messages: Persons with DM with good compliance to diet and exercise were found to have poor attendance at the DRS programme. Targeted advertising is required to raise awareness of diabetic retinopathy.